Variability of organic nitrogen and its role in regulating phytoplankton in the eastern Arabian Sea. (April 2019) - Shetye, Suhas S.; Kurian, Siby; Naik, Hema; Gauns, Mangesh; Chndrasekhararao, A.V.; Kumar, Ashwini; Naik, Bhagyashri
Abstract: The relative importance of organic nitrogen (ON) and inorganic nitrogen (IN) as nitrogen sources for the phytoplankton communities were studied through a seasonal time series of nitrogen species in the eastern Arabian Sea. Seasonal data on nitrogen species showed that ON dominates the system throughout the year and account for >90% of the total nitrogen (TN) during north east monsoon (NEM). The average ON concentration in the study region was 11.5 μM during NEM as compared to 7.2 μM during south west monsoon (SWM). The contribution of picoplankton to the total phytoplankton pool ( f pico ) increased from 19% during SWM to 36% in NEM. Along with cyanobacteria, the diatoms Thalassionema nitzchoides and Thalassiosira sp. and among the dinoflagellates Pronoctiluca sp. were found to proliferate in ON rich waters. We suggest atmospheric deposition, riverine-input, resuspension of bottom sediment and ground water intrusion as the possible sources of ON in the study region.